2020
DOI: 10.1111/pcmr.12919
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CRISPR‐Cas9 screens identifies genetic dependencies in melanoma

Abstract: Early-stage cutaneous melanoma can be effectively cured by surgical removal, but once metastasized patient prognosis is poor (Schadendorf et al., 2018). Increased signaling activity of the mitogen-activated protein kinase (MAPK) pathway is a hallmark of melanoma and can be attributed to mutations in the BRAF, NRAS, KIT, or NF1 genes. These oncogenic mutations commonly occur in the early stages of melanoma development (Davies et al., 2002;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…Detailed understanding of the role of genes and proteins in key signaling pathways in melanoma development has led to the designation of new targets for the treatment of melanoma. Recently, analysis of CRISPR-CAS9 screens has identified genes that have not previously been associated with melanoma growth and that can be targeted using available inhibitors, thus opening new treatment strategies that may be explored in the near future as potential therapeutic targets [ 167 ]. Furthermore, in the future, more clinical trials and more data on OS and response rates need to be collected to find the best combination treatment and the best possible sequence of combination therapy to manage the complexity of melanoma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed understanding of the role of genes and proteins in key signaling pathways in melanoma development has led to the designation of new targets for the treatment of melanoma. Recently, analysis of CRISPR-CAS9 screens has identified genes that have not previously been associated with melanoma growth and that can be targeted using available inhibitors, thus opening new treatment strategies that may be explored in the near future as potential therapeutic targets [ 167 ]. Furthermore, in the future, more clinical trials and more data on OS and response rates need to be collected to find the best combination treatment and the best possible sequence of combination therapy to manage the complexity of melanoma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis was identical to that described in Christodoulou et al . [ 37 ], except that we used data on all 29 melanoma cell lines released by the Broad Institute [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the P values were adjusted for multiple testing using the FDR method. The analysis was identical to that described in Christodoulou et al [37], except that we used data on all 29 melanoma cell lines released by the Broad Institute [34].…”
Section: Gene Dependency Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…shown that the genetic inactivation of DUSP4 reduced the proliferation of melanoma cells, thus making DUSP4 an interesting therapeutic target (Christodoulou et al, 2021). DUSP4 is expressed in different tissues, including the eye, and more importantly in retinal BCs (Supplementary Table S6,.…”
Section: Bdnf (Mim# 113505) Encoding Brain-derived Neurotrophic Facto...mentioning
confidence: 99%